Prevalence of adverse cardiovascular events in pediatric cardiomyopathies: an analysis of 110 patients followed at a long-standing tertiary care paediatric centre. (25th November 2020) - Pagano, M; Fumagalli, C; Girolami, F; Spinelli, V; Passantino, S; Brambilla, A; Morrone, A; Donati, M.A; Olivotto, I; Favilli, S
Abstract: Introduction: Pediatric cardiomyopathies (CMP) are disorders of the morphology and function of the heart, with a greater heterogeneity concerning etiology and clinical presentation than adult CMP. The assessment of etiology and genetic status is of paramount importance for prognosis, family screening, and therapeutic choices. Purpose: To report clinical presentation, etiology, and outcome of a cohort of children diagnosed with CMP followed at tertiary care pediatric referral centre. Methods: We retrospectively reviewed clinical, laboratory and imaging data of all patients referred to our cardiomyopathy centre from May 2008 to May 2019 for pediatric CMP (<18 years). CMP due to arrhythmic disorders, toxic agents' exposure, rheumatic conditions and maternal disease (i.e. maternal diabetes) were excluded. Primary endpoint was a composite of major adverse cardiovascular events (MACE: cardiovascular death, heart failure [HF] hospitalization, arrhythmic events, need for surgery or heart transplant referral). Results: We enrolled 110 patients (65 males, age at diagnosis 67±71 months). Hypertrophic cardiomyopathy (HCM, N=48, 44%) was most frequent, followed by dilated cardiomyopathy (DCM, N=35 32%) and left ventricular non-compaction phenotype (LVNC, N=12, 11%). Mixed phenotype (N=7, 6%) and restrictive cardiomyopathy (RCM, N=3, 3%) were less common. No cases of arrhythmogenic right ventricular cardiomyopathy (ARVC) were detected. Five genotype-positive patients presented with negative clinical phenotype. A diagnosis was confirmed in all patients; the most common was sarcomere disease (30%, N=33) followed by metabolic (28%, N=31) disease, genetic syndromes (11%, N=12), neuromuscular (7, 3%, N=8) diseases, and post-myocarditis cases (4, 5%, N=5). Twenty-one patients (19%) were identified as idiopathic. At referral, 4, 5% of children presented with NYHA class III/IV. At 35 [14–72] months, 4 (3.7%) patients required ICD implantation, 8 (7.4%) underwent cardiac surgery, and 1 (1%) underwent heart transplant. Furthermore, 28 (26%) patients required hospitalization due to acute HF, with DCM patients being at higher risk (p<0.01), 7 (6.8%) experienced arrhythmic events and 4 (3.9%) had syncope. Overall, 13 (12%) died (7 with metabolic disorders, 3 with genetic syndromes, 1 with a sarcomeric mutation, 1 post myocarditis, and 1 idiopathic). Conclusions: In our cohort, HCM was the most common cause of pediatric CMP followed by DCM and non-compaction. MACE were present in 41% of patients. While HCM had a less severe phenotype (characterized by a higher arrhythmic burden), DCM was characterized by a higher prevalence of HF hospitalizations. DCM, inborn errors in metabolism and genetic syndromes had the worst outcome in terms mortality and heart failure long term. Widespread availability of genetic testing provides several benefits to the clinician, confirming diagnosis in ambiguous cases and defining etiology in order to guide management and identifying relatives at risk. Funding Acknowledgement: Type of funding source: None